Cinematographic Composition in Building the Dramatization of Sadness in "Akhir Tak Bahagia” Music Video - William Sanjaya; Hendi Thamrin; Inne Chaysalina; Ferry Agustian Sukarno (Judikatif: Jurnal Desain Komunikasi Kreatif, 2025)
Video is a form of mass media that has characteristics like a film. Music videos are videos that have a short duration as an accompaniment to music or songs. "Akhir Tak Bahagia" is a music video that tells the story of someone who loves the wrong person in her life. " Akhir Tak Bahagia " applied visual compositions in building a dramatization of sadness so that the message of the song's lyrics can be conveyed to the audience. This research discusses the application of visual composition in creating a dramatization of sadness to support the message in the music video "Akhir Tak Bahagia". The research method used is qualitative, while the approach uses a purposive sampling approach. The theory used is the theory of visual composition proposed by Gustavo Mercado. The research was carried out by elaborating the song lyrics, visual composition, and meaning as an emphasis on the dramatization of sadness, which supports the message of the lyrics of the music video song "Akhir Tak Bahagia". From the research conducted, it was concluded that the application of visual composition was in the form of a rule of thirds with empty areas and visual balance that showed scenes of sweet memories from the main character. The scene shows sweet, painful memories. On the other hand, the composition takes the form of a rule of thirds with a narrow area and visual continuity applied to the scene when Misellia sings a song with sadness. By applying this visual composition, the dramatization of sadness is conveyed so that the message of the song lyrics can be conveyed.